Sastra Pesantren dalam Lintasan Sejarah - Roni Tabroni (IAIN Syekh Nurjati Cirebon, 2019)
Abstract This article discusses the literature of pesantren and the themes that surround it since the beginning of the emergence of this institution of traditional Islamic education in the 18th century until now. Pesantren literature is defined as a literature that talks about the habits of pesantren. In addition, pesantren literature can be defined as a literary work in which there is a psychological side of pesantren with a strong religious style. This research uses the historical method such as heuristic-archive research, and literature review- critics, interpretation and historiography to traces the beginning of the existence of pesantren literature at the beginning of its founding and the development of its themes up to now. This theory is then combined with the theory of identity to give identity to the works of pesantren literature since its emergence in the early 18th century until which emerged today. In addition, this study uses literature study by selecting several literary works of pesantren to determine the identity and the themes contained in it. The results show that pesantren literature has lived and developed since the emergence of Tegalsari pesantren in Ponorogo in 1742. At the beginning of the emergence of pesantren is often used as the place of the poets to produce works. The theme of the story revolves around the archipelago, Middle East and India in Sufi / Sufism. Sufi values / Sufism will be the hallmark of pesantren literature from the beginning to appear until now. These themes then undergo development and expansion with the emergence of literary pesantren genre pop and subversive these days by still making the pesantren as the center of the story and the values of Sufism as the foundation. Keywords: Literature, Pesantren, Identity, Religious.